The effect of indigofera leaf meal on production performance and eggs quality of Coturnix coturnix japonica - Zakariya, Abu; Nur Khamid, Muh; Aryanti, Isnaini; Wardi, Wardi (Jurnal Ilmu Peternakan Terapan, 2024)
The research aimed to determine the effect of using indigofera leaf meal on quail eggs performance and physical quality. The research was conducted from March to May 2023 at the Poultry Laboratory of Yogyakarta Magelang Agricultural Development Polytechnic (POLBANGTAN). The research used a completely randomized design (CRD) with 4 treatments and 5 replications, using 200 blaster quails. Treatments included P0 (without Indigofera leaf meal), P1 (7.5% Indigofera leaf meal), P2 (15% Indigofera leaf meal), and P3 (22.5% Indigofera leaf meal). Parameters observed included feed consumption, egg production, egg weight, egg index, shell thickness, albumen index, egg yolk index, haugh units, and egg yolk color score. The research data was analyzed using ANOVA and Kruskal Wallis analysis. A further Duncan Multiple Range Test (DMRT) was carried out if the treatment had a significant difference. Based on the results, the use of Indigofera leaf meal at different levels had no significant effect (P>0.05) on egg production, feed consumption, egg weight, albumen index, egg yolk index, and haugh units. However, it significantly affected (P<0.05) shell thickness, egg index, and yolk color score. The research concluded that feeding Indigofera leaf meal up to 22.5% can be used because it does not affect production performance and improves egg quality.